Digitizing and Preserving Law School Recordings: A Duke Law Case Study - White, Hollie; Bordo, M.; Chen, S. (Routledge, 2015)
Written as a case study, this article outlines Duke Law School Information Services’ video digitization, preservation, and access initiative. This article begins with a discussion of the case study environment and the cross-departmental evaluation of in-house video production and processing workflows. The in-house preservation reformatting process and new collection policies that resulted from this evaluation are presented next. This is followed by descriptions of the programmatic approach used to coordinate multiple access venues by focusing on Python scripting and Google Data APIs to deliver consistent content and metadata. The article concludes with a discussion on the concept of best practices.